A Literature Review of CO2, Natural Gas, and Water-Based Fluids for Enhanced Oil Recovery in Unconventional Reservoirs - Burrows, Lauren C; Haeri, Foad; Cvetic, Patricia; Sanguinito, Sean; Shi, Fan; Tapriyal, Deepak; Goodman, Angela; Enick, Robert M (Energy & fuels, 2020)
Primary oil recovery from fractured unconventional formations, such as shale or tight sands, is typically less than 10%. The development of an economically viable enhanced oil recovery (EOR) technique applicable to unconventional liquid reservoirs (ULRs) would lead to tremendous increases in domestic oil production. Although injection techniques such as waterflooding and CO2 EOR have proven profitable in conventional formations for decades, EOR in ULRs presents a far more difficult challenge. The extremely low permeability and mixed wettability of unconventional formations are the foremost obstacles to success. Because of the challenges associated with water-based EOR techniques (a.k.a., chemical EOR) in shale, several nonaqueous injection fluids have been considered, including CO2, natural gas, and (to a lesser degree) nitrogen. All these fluids have significantly lower viscosities than water, allowing them to more easily penetrate shale nanopores. Unlike water, they also each possess some degree of miscibility with oil, which enables the gas to extract oil through a combination of mechanisms. Based on laboratory-scale experimentation, CO2 and rich natural gas (methane-rich natural gas containing high concentrations of ethane, propane, and butane) are the most promising EOR fluids. The interpretation of results from field tests in the Bakken and Eagle Ford formations have been complicated by interference of frac-hits or well-bashing caused by hydraulic fracturing at nearby wells. In this review we cover mechanisms, laboratory experiments, numerical simulations, and field tests involving high-pressure CO2, natural gas, ethane, nitrogen, and water.